Numerical simulation of liquids draining from a tank using openFOAM - Mohd. Sakri, Fadhilah (2015)
Draining a liquid from a cylindrical tank is numerically simulated using OpenFOAM. OpenFOAM is an open source CFD package and it becomes increasingly popular among the academician and also industries. In this paper, comparisons with theoretical and results from previous published data confirmed that Open-FOAM is able to simulate the liquids draining very well. This is done using the gas-liquid interface solver available in the standard library of OpenFOAM.